Dismantling, disintegration or continuing stealthy integration in European Union environmental policy?. (2nd April 2020) - Lenschow, Andrea; Burns, Charlotte; Zito, Anthony
Abstract: This symposium assesses the trajectory of European Union (EU) environmental policy and integration in light of the rising pressure for policy dismantling and disintegration. This introductory article discusses the literature and the mixed evidence of EU environmental policy dismantling. Building on the three symposium articles, we investigate the role of the European Commission in this process, evaluating its role as a general 'motor of integration' and more specifically as an environmental policy entrepreneur. We find that the current political context does push the Commission to reconsider its entrepreneurial role and adopt the role of a 'normalized bureaucracy'. Nonetheless, organizational features, such as new hierarchies and presidential leadership, and ideas that frame policy initiatives explain continued policy evolution and resistance to outright dismantling. Scholars should also pay close attention to implementing measures and patterns of enforcement to detect the more subtle policy shifts.